(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2023)
This article describes the unique features of the American education system, one of the most developed countries in the world, the types of education and their stages in a sequence. It reveals a number of features of preschool education, primary school, secondary school, and higher education.